MODEL ASUHAN KEPERAWATAN PROFESINAL DI RUANG PAMENANG RSUD GAMBIRAN KOTA KEDIRI - Yoyok Yulianto; Slamet Jayadi; Ali Humardani; Yuly Peristiowati; Wahyu Agung (STIKes Maharani Malang, 2022)
Introduction: The strategy to increase the role and function of nurses in providing nursing services is to evamp nursing management, so that optimal management factors can be used as an effort to improve nursing service delivery and ensure patient satisfaction. This study aims to describe the practice of nursing residency management towards improving nursing care service efforts, and the implementation of innovations about nursing management strategies for the implementation of professional nursing care (MAKP) TIM in the Pamenang room of Gambiran Hospital, Kediri. Method: The team's MAKP method was applied in the Pamenang Room of Gambiran Hospital, Kediri City. SWOT analysis to determine the priority of the problem. Result: The results of the Pamenang Room SWOT analysis found priority issues: Discharge Planning, Nursing Round, Nursing Documentation, M3-METHOD (MAKP), M1 (Employment), M2 (Facilities and Infrastructure), Supervision, Weighing in, and Drug Centralization. Discussion: Inadequate discharge planning in the room, Unavailability of patient leaflets when returning home, Not yet optimal health education for patients/families, Nursing Rounds cannot be carried out in the treatment room, Characteristics of staff who meet qualifications are not evenly distributed, MAKP has not been implemented optimally, Number of staff is not balanced with the number of patient dependence levels, There is no standardized format for nursing interventions, There is no computerized documentation system, Some employees have unclear job descriptions, MAKP has not been implemented properly, Supervision has not been carried out, Implementation of the team model is not appropriate, Nurses manage all patients, Nursing rounds has not been implemented, facilities and infrastructure for maintenance actions are available in sufficient and good condition but insufficient. Keywords: Coronary Heart Disease, Phase 1 Cardiac Rehabilitation Program, Roy Adaptation Model Theory